Preparation of a Trp-BODIPY fluorogenic amino acid to label peptides for enhanced live-cell fluorescence imaging - Mendive-Tapia, Lorena; Subiros-Funosas, Ramon; Zhao, Can; Albericio, Fernando; Read, Nick D; Lavilla, Rodolfo; Vendrell, Marc (Nature protocols, 2017)
Fluorescent peptides with excellent target specificity are useful imaging probes. This protocol describes the synthesis of a tryptophan-based fluorogenic amino acid (Fmoc-Trp(C 2 -BODIPY)-OH) and its incorporation into peptides for live-cell imaging. Fluorescent peptides are valuable tools for live-cell imaging because of the high specificity of peptide sequences for their biomolecular targets. When preparing fluorescent versions of peptides, labels must be introduced at appropriate positions in the sequences to provide suitable reporters while avoiding any impairment of the molecular recognition properties of the peptides. This protocol describes the preparation of the tryptophan (Trp)-based fluorogenic amino acid Fmoc-Trp(C 2 -BODIPY)-OH and its incorporation into peptides for live-cell fluorescence imaging—an approach that is applicable to most peptide sequences. Fmoc-Trp(C 2 -BODIPY)-OH contains a BODIPY (4,4-difluoro-4-bora-3a,4a-diaza- s -indacene) fluorogenic core, which works as an environmentally sensitive fluorophore, showing high fluorescence in lipophilic conditions. It is attached to Trp via a spacer-free C–C linkage, resulting in a labeled amino acid that can mimic the molecular interactions of Trp, enabling wash-free imaging. This protocol covers the chemical synthesis of the fluorogenic amino acid Fmoc-Trp(C 2 -BODIPY)-OH (3–4 d), the preparation of the labeled antimicrobial peptide BODIPY-cPAF26 by solid-phase synthesis (6–7 d) and its spectral and biological characterization as a live-cell imaging probe for different fungal pathogens. As an example, we include a procedure for using BODIPY-cPAF26 for wash-free imaging of fungal pathogens, including real-time visualization of Aspergillus fumigatus (5 d for culturing, 1–2 d for imaging).